Biomedical properties of novel mononuclear phosphanegold(I) dithiocarbamates - Chen, Bao Jing (2017)
The notable achievement of medicinal inorganic chemistry in particular transition metal and the development of medicinal metal complexes is extended beyond platinum class. Gold complexes aims to solve chemoresistance and toxic side effects of platinum have inspired the idea of synthesizing mononuclear phosphanegold(I) dithiocarbamate complexes series, R3PAu[S2CN(CH2CH2OH)2], R = phenyl (Ph) (1a), cyclohexyl (Cy) (1b) and ethyl (Et) groups (2a and 3a). Antibacterial screening of the four complexes by antimicrobial susceptibility tests encompasses disc diffusion, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) determination and time kills assay allowed the identification of antibacterial properties against 24 Gram-positive and Gram-negative pathogens. The antibacterial activity of the complexes was found to differ among each other, either broad range or specific and bacteriostatic or bactericidal. Anticancer properties of the complexes was demonstrated in 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and flow-cytometry, showed to be effective against breast, lung and colorectal cancer cell lines with identified IC50 in μM over 24 hours interaction. The anticancer activity also found to be associated with the ability to inhibit breast cancer invasion and migration through BioCoat™ Matrigel™ Invasion Chamber and scratch assay. Investigation of the cell death mode induced by the four complexes through acridine orange (A0)/ propidium iodide (PI) double staining and DNA fragmentation, indicated the apoptosis event was occurring with the observation of apoptotic morphological features and fragmented DNA. Complexes 1a, 1b, 2a, and 3a resulted apoptosis were further assessed with fluorescent detection. Translocation of phosphatidylserine (PS), cell cycle arrest, and increase caspases expressions provided the hint of increase mitochondrial membrane potential related to intrinsic and extrinsic pathways. Data was then supported by RT2 Profiler TM PCR array which involve the study of 84 apoptotic genes, exhibited the upregulation of p53/p73 and higher expression of pro-apoptotic genes over anti-apoptotic genes. Toxicity of the complexes were determined through in vivo survival assay on Caenorhabditis elegans and in vitro MTT assay on human embryonic kidney cell (HEK293) and rat myocardium cell (H9C2). Result showed the complexes at low dosage showed generally not effect on lifespan but high dosage cause lifespan reduction. However, all four complexes displayed low toxicity on HEK293 and H9C2 with higher IC50 than cancer cells. Apart from that, mutagenicity of the complexes were evaluated through Ames test and showed lack of mutagenic potential. Based on in vitro antibacterial and anticancer potency, all four complexes were arranged in the descending order 2a > 3a > 1a > 1b. However, the four complexes exhibited toxicity in the descending order 1b > 1a > 2a > 3a. Complex 2a represented the complex with greatest antibacterial and anticancer activities and lower toxic than complex 3a. As a conclusion, mononuclear phosphanegold(I) dithiocarbamates have excellent antibacterial and anticancer activities which induce both mitochondria and death receptors apoptotic pathways with generally low toxicity and not mutagenic.